Industriales de Buenos Aires e industriales del interior. Los manufactureros y los azucareros tucumanos a finales del siglo XIX y principios del XX. - Sánchez Román, José Antonio (Revista Complutense de Historia de América, 2001)
Recent literature has brought up and old issue about the agro-export period in Argentina: the conflicts between landlords and manufacturers, but creating a new version. As the traditional historiography stated, there were differences between landlords and industrialists; they did not belong to the same group, but it was not true that landlords controlled the political power. On the other hand, industrialists were not the weak group that the traditional literature had depicted. The influenced the government to get customs duties. Therefore, we cannot say anymore that anti-industrial policies and the overwhelming power of «estancieros» were the major features of Argentine agro-export model. The aim of this article is to introduce a new variable in the analysis of the issue of the characteristics of Argentine economic elites. How does our image of the Argentine economic elites and particularly of the industrialists change if we compare them with another group? The case of the sugar producers is quite relevant because they were a very powerful group, always claiming for protection and complaining about the free-trade trends of the national government an the Litoral elites. Sugar manufactuers became sometimes the most outstanding speakers for the «national industry», but on the other hand their relationship with other industrial producers was complex. In spite of seemingly shared interests, like protectionism, the disagreements between both groups weremore frequent than expected.
Keywords: Argentine history; Economic History; entrepreneurs; manufacturers; sugar industry